1977
DOI: 10.1073/pnas.74.10.4481
|View full text |Cite
|
Sign up to set email alerts
|

Induction of DNA synthesis in BALB/c 3T3 cells by serum components: Reevaluation of the commitment process

Abstract: Serum contains a growth factor derived from platelets and also growth factors derived from platelet-poor plasma. Extracts of heated (1000) human platelets function synergistically with platelet-poor plasma to induce DNA synthesis in quiescent, density-inhibited BALB/c 3T3 cells. Platelet-poor plasma alone did not induce DNA synthesis. Cells exposed to platelet extracts became competent to enter the cell cycle, but the rate of entry into the S phase depended upon the concentration of platelet-poor plasma. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
413
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 616 publications
(427 citation statements)
references
References 11 publications
14
413
0
Order By: Relevance
“…Using subsaturating concentrations of growth factors, Pledger, Stiles, Antoniades, and Sher demonstrated that in Balb/c 3T3s cell cycle progression required the input of two di erent types of factors (Pledger et al, 1977(Pledger et al, , 1978Stiles et al, 1979b). Growth factors such as PDGF or FGF made the cells competent, but did not drive them into S phase.…”
Section: Revisiting Competence and Progressionmentioning
confidence: 99%
“…Using subsaturating concentrations of growth factors, Pledger, Stiles, Antoniades, and Sher demonstrated that in Balb/c 3T3s cell cycle progression required the input of two di erent types of factors (Pledger et al, 1977(Pledger et al, , 1978Stiles et al, 1979b). Growth factors such as PDGF or FGF made the cells competent, but did not drive them into S phase.…”
Section: Revisiting Competence and Progressionmentioning
confidence: 99%
“…As the first step towards proliferation quiescent cells initially require growth factors (see Fig. 11, such as platelet-derived growth factor (PDGF) or fibroblast growth factor (FGF), for initiating early regulatory processes, referred to as reaching "competence" [Pledger et al, 1977;Scher et al, 19791. In the presence of epidermal growth factor (EGF) and insulin-like growth factor-I (IGF-I), competent cells can progress to the next stage in G1, termed the "V" point [Leof et al, 19831. Cells at the "V" point exhibit a rapid rate of protein synthesis [Rossow et al, 19791 and soon reach the "restriction" point "R" [Pardee, 19741. In the presence of IGF-I or insulin, these cells will then commence DNA synthesis without any additional requirement for growth factors, tran-P rog ressi o n { Factors IGF-Vinsulin IL-2, etc.…”
Section: Competence Factorsmentioning
confidence: 99%
“…Mitogenic peptide growth factors, such as platelet-derived growth factor, insulin like growth factor-I, and EGF, are among the best studied examples of such external cell cycle regulators (Pardee, 1989;Sporn and Roberts, 1990). Although the exact roles of these growth factors seem to be somewhat variable in different fibroblast cell lines, it is clear that they are required to stimulate entry of quiescent (G0-synchronized) fibroblasts into the cell cycle and progression of the cells through most of G1 (Pledger et al, 1977;Pardee, 1989). Transit from late G1 into S is independent of mitogenic growth factor action (Pledger et al, 1977;Yen and Pardee, 1978;Rossow et al, 1979).…”
Section: Ell Cycle Progression In Nontransformed Fibroblastsmentioning
confidence: 99%
“…Although the exact roles of these growth factors seem to be somewhat variable in different fibroblast cell lines, it is clear that they are required to stimulate entry of quiescent (G0-synchronized) fibroblasts into the cell cycle and progression of the cells through most of G1 (Pledger et al, 1977;Pardee, 1989). Transit from late G1 into S is independent of mitogenic growth factor action (Pledger et al, 1977;Yen and Pardee, 1978;Rossow et al, 1979). When compared to the growth factors discussed above, the effects of TGF-/$1 on fibroblast proliferation seem quite distinct.…”
Section: Ell Cycle Progression In Nontransformed Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation